The The Impact of Green Price, Green Promotion, and Green Place on the Economy of Communities in Tourism Areas through Environmental Sustainability Entering the New Normal - Nanik Wahyuningtiyas; Abdullah Syakur Novianto (Quantitative Economics and Management Studies, 2023)
This study aims to analyze and explain (1) determine the effect of Green Marketing on environmental sustainability in tourists; (2) To find out the effect of Green Marketing on the economy of the community in tourists; (3) To determine the effect of environmental sustainability on the economy of the community in tourist areas; (4) To determine the effect of Green Marketing (green price, green promotion and green place) on the economy of the community in tourist areas through environmental sustainability as an intervening variable. This study uses a data collection method with a questionnaire with a quantitative approach. The population that becomes the object of research is tourists who visit tourist areas in Malang Raya. Testing the analysis using SEM with the Smart PLS analysis tool. Green price does not directly affect the sustainability of the environment, while green promotion and green place directly affect environmental sustainability. Green prices, green promotions, and green places do not have a direct effect on the community economy, while environmental sustainability has a direct effect on the community economy. Green prices do not indirectly affect the community economy through environmental sustainability, while green promotion and green places indirectly affect the community. Community economy through environmental sustainability.